2003
DOI: 10.1088/1126-6708/2003/04/054
|View full text |Cite
|
Sign up to set email alerts
|

KamLAND bounds on solar antineutrinos and neutrino transition magnetic moments

Abstract: We investigate the possibility of detecting solar electron antineutrinos with the KamLAND experiment. These electron antineutrinos are predicted by spin-flavor oscillations at a significant rate even if this mechanism is not the leading solution to the SNP.KamLAND is sensitive to antineutrinos originated from solar 8 B neutrinos. From KamLAND negative results after 145 days of data taking, we obtain model independent limits on the total flux of solar electron antineutrinos Φ( 8 B) < 1.1 − 3.5 × 10 4 cm −2 s −1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…However, the recent KamLAND experiment [10] has shown that the large mixing angle (LMA) MSW solution is the most favourable one; the RSF mechanism is suppressed at the subdominant level. From the KamLAND negative results for the solar antineutrino search, an upper bound on the neutrino magnetic moment is obtained, µ ν 1 × 10 −12 µ B , where µ B is the Bohr magneton [11]. This upper bound is comparable to the most stringent limit from the stellar cooling argument, µ ν (1-4)×10 −12 µ B [12].…”
Section: Introductionmentioning
confidence: 78%
“…However, the recent KamLAND experiment [10] has shown that the large mixing angle (LMA) MSW solution is the most favourable one; the RSF mechanism is suppressed at the subdominant level. From the KamLAND negative results for the solar antineutrino search, an upper bound on the neutrino magnetic moment is obtained, µ ν 1 × 10 −12 µ B , where µ B is the Bohr magneton [11]. This upper bound is comparable to the most stringent limit from the stellar cooling argument, µ ν (1-4)×10 −12 µ B [12].…”
Section: Introductionmentioning
confidence: 78%
“…We show that, under reasonable assumptions, such bound is comparable to the best astrophysical limit that follows from stellar cooling arguments [18]. An alternative analysis of the KamLAND data [1] using the ''delta-correlated'' model for the solar random magnetic field was done in [19].…”
Section: Introductionmentioning
confidence: 73%
“…However, the recent KamLAND experiment [9] has shown that the large mixing angle (LMA) MSW solution is the most favourable one; the RSF mechanism is suppressed at the subdominant level. From the KamLAND negative results for the solar antineutrino search, an upper bound on the neutrino magnetic moment is obtained, µ ν 1 × 10 −12 µ B , where µ B is the Bohr magneton [10]. This upper bound is comparable to the most stringent limit from the stellar cooling argument, µ ν (1-4)×10 −12 µ B [11].…”
Section: Ahep-2003mentioning
confidence: 78%